2022
DOI: 10.1002/lt.26460
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic cardiomyopathy: Appraisal of the original and revised criteria in predicting posttransplant cardiac outcomes

Abstract: Cardiovascular disease (CVD) significantly contributes to morbidity and mortality after liver transplantation (LT). Cirrhotic cardiomyopathy (CCM) is a risk factor for CVD after transplant. CCM criteria were originally introduced in 2005 with a revision proposed in 2020 reflecting echocardiographic technology advancements. This study assesses the two criteria sets in predicting major adverse cardiac events (MACE) after transplant. This single‐center retrospective study reviewed adult LT recipients between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…However, differences in all-cause mortality were not found, as in our study. (32,33) Many of the studies we found in our systematic review reported con icting results on a relationship between LVDD and worse outcomes; however, we found high heterogeneity in the criteria used to de ne LVDD between studies, which include the WGC criteria, (15,30)the 2009 ASE criteria (20,27), and isolated parameters of diastolic function (TR, LAVI, E/e'). (22)(23)(24)(25)31)Given the high variability in the criteria employed, we could not include most of these studies in our meta-analysis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, differences in all-cause mortality were not found, as in our study. (32,33) Many of the studies we found in our systematic review reported con icting results on a relationship between LVDD and worse outcomes; however, we found high heterogeneity in the criteria used to de ne LVDD between studies, which include the WGC criteria, (15,30)the 2009 ASE criteria (20,27), and isolated parameters of diastolic function (TR, LAVI, E/e'). (22)(23)(24)(25)31)Given the high variability in the criteria employed, we could not include most of these studies in our meta-analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Another study (33) compared the WCG criteria to the CCMC criteria to determine which were better at predicting post-LT MACE. Multivariable analysis showed that patients that ful lled CCMC criteria were at increased risk of developing MACE (HR, 1.93; 95% CI, 1.05-3.56; p = 0.04) after controlling for covariates.…”
Section: Lvdd and Postoperative Cardiovascular Complicationsmentioning
confidence: 99%
“…In addition, it has been estimated that as many as 50% of patients undergoing LT are found to have some degree of cirrhotic cardiomyopathy, which is associated with a greater severity of liver disease 30. Cirrhotic cardiomyopathy could potentiate an increased risk of posttransplant cardiac complications, increasing the complexity and duration, and therefore cost of care associated with the transplant hospitalization 31,32. As waitlist times increase, patients may be more likely to develop comorbid illnesses that require multidisciplinary care coordination and contribute to increased costs related to LT hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…[30] Cirrhotic cardiomyopathy could potentiate an increased risk of posttransplant cardiac complications, increasing the complexity and duration, and therefore cost of care associated with the transplant hospitalization. [31,32] As waitlist times increase, patients may be more likely to develop comorbid illnesses that require multidisciplinary care coordination and contribute to increased costs related to LT hospitalization. This is potentially reflected in our analysis, which indicates increasing LT-related incidence and costs among patients with ≥ 2 comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Liver Transplantation , Spann et al have approached this question by comparing the definitions of CCM with clinical output in terms of MACE and cardiac function. [ 7 ] In a single‐center retrospective study, the authors included 210 of 1165 patients with pre–liver transplantation echocardiography and eligibility criteria. The authors applied MACE comprising arrythmia, heart failure, cardiac arrest, or cardiac death as primary composite endpoints.…”
mentioning
confidence: 99%